2022
DOI: 10.1002/jcla.24288
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of ELISA and dot blot assay for TSH‐receptor antibody detection in Graves’ disease

Abstract: Background Graves’ disease (GD) is an autoimmune disease, and it accounts for major cases of hyperthyroidism. Antibody against thyroid‐stimulating hormone receptor/TSHR (TRAb) is responsible for hyperthyroidism and is considered as a diagnostic marker for GD. Therefore, we developed a recombinant protein of human TSHR‐169 (hTSHR‐169), which was specifically recognized TRAb in the serum of GD patients and then compare the diagnostic performance between ELISA and dot blot of TRAb tests for their ability to diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In a recent study comparing two third-generation immunoassays for the measurement of TSHrAb, a high agreement between the two methods was obtained (kappa; 0.82) [ 22 ]. Another recent study demonstrated slightly better diagnostic performance of third-generation enzyme-linked immunosorbent assay (ELISA) methods than second-generation ones [ 23 ]. Recent studies have also demonstrated the utility of a few newer methods for the measurement of TSHrAb such as one-step third-generation radioimmunoassay and dot-blot method are useful, albeit with modestly lower diagnostic accuracy of the latter method [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study comparing two third-generation immunoassays for the measurement of TSHrAb, a high agreement between the two methods was obtained (kappa; 0.82) [ 22 ]. Another recent study demonstrated slightly better diagnostic performance of third-generation enzyme-linked immunosorbent assay (ELISA) methods than second-generation ones [ 23 ]. Recent studies have also demonstrated the utility of a few newer methods for the measurement of TSHrAb such as one-step third-generation radioimmunoassay and dot-blot method are useful, albeit with modestly lower diagnostic accuracy of the latter method [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with immunoblotting, ELISA typically has higher sensitivity and throughput, and requires a relatively low amount of materials [24][25][26]. Therefore, we chose ELISA as the detection platform.…”
Section: Optimization Of Elisa Conditions For the Detection Of Tfam-dpcsmentioning
confidence: 99%